Analisis Produktivitas Tenaga Kerja dengan Metode Time Study pada Proyek Pedestrian Depan Stadion Surajaya Lamongan - Darmawan, Mirza Agung; Agustapraja, Hammam Rofiqi; Arif, Samsul (Jurnal Talenta Sipil, 2025)
Human resources are very important in the work environment, especially in the construction sector. Without a qualified and productive workforce, the project results will not be satisfactory. This research aims to observe the productivity of workers while constructing the pedestrian in front of the Surajaya Stadium in Lamongan, focusing on rebar work, formwork installation, and concreting using the time study method. The initial stage involves analyzing the project and collecting data that will be used as material for observing labor productivity. The productivity for foundation rebar work is recorded at 134.86 kg/person/day, and for column rebar work at 96.84 kg/person/day. The productivity value for formwork also varies, reaching 351.82 m²/person/day for slab formwork work.. Casting work has varying productivity, for example 9.10 m3/person/day for foundation casting. Several factors that affect productivity are the lack of worker skills, hot weather, and obstacles at the project site. The productivity of rebar work, formwork installation, and casting in this project is low due to the lack of worker skills, hot weather causing fatigue, and access barriers. To improve efficiency, training for workers, scheduling work hours, and managing the surrounding environment are necessary.